A Case Report of ST-Segment Elevation Myocardial Infarction due to Emotional Stress Caused by Spontaneous Coronary Artery Dissection in A Young Male - Ali, Farman; Arshad, Khurram; Latif, Rabia; Ullah, Aman; Alamro, Yazan; Raheela, FNU; Zafarullah, FNU (Cardiology and Cardiovascular Medicine, 2024)
Spontaneous Coronary Artery Dissection (SCAD) is a rare condition that can present as an Acute Coronary Syndrome (ACS), including ST-Segment Elevation Myocardial Infarction (STEMI). It is often underdiagnosed for various reasons. It is frequently reported in young females in association with fibromuscular dysplasia as an underlying condition. In literature, only a few cases of SCAD have been reported associated with emotional stress. In our case, a 29-year-old male who presented with acute onset chest pain and initial emergency department presentation was consistent with STEMI.